Preservative solution that stabilizes erythrocyte morphology and leukocyte viability under ambient conditions - Rebecca D. Sandlin (Scientific Reports, 2017)
Abstract The deterioration of whole blood ex vivo represents a logistical hurdle in clinical and research settings. Here, a cocktail preservative is described that stabilizes leukocyte viability and erythrocyte morphology in whole blood under ambient storage. Neutrophil biostabilization was explored using a sophisticated microfluidic assay to examine the effectiveness of caspase inhibition to stabilize purified neutrophils. Following 72 h ambient storage, neutrophils remained fully functional to migrate towards chemical cues and maintained their ability to undergo NETosis after stimulation. Furthermore, stored neutrophils exhibited improved CD45 biomarker retention and reduced apoptosis and mortality compared to untreated controls. To stabilize erythrocyte morphology, a preservative solution was formulated using Taguchi methods of experimental design, and combined with the caspase inhibitor to form a whole blood cocktail solution, CSWB. CSWB was evaluated in blood from healthy donors and from women with metastatic breast cancer stored under ambient conditions for 72 h. CSWB-treated samples showed a significant improvement in erythrocyte morphology compared to untreated controls. Leukocytes in CSWB-treated blood exhibited significantly higher viability and CD45 biomarker retention compared to untreated controls. This 72 h shelf life under ambient conditions represents an opportunity to transport isolates or simply ease experimental timelines where blood degradation is problematic.